Graphene-encapsulated nickel–copper bimetallic nanoparticle catalysts for electrochemical reduction of CO2 to CO. Issue 76 (24th August 2020) - Xu, Chaochen; Vasileff, Anthony; Jin, Bo; Wang, Dan; Xu, Haolan; Zheng, Yao; Qiao, Shi-Zhang
Abstract : High CO selectivity for the CO2 electroreduction reaction was achieved on Ni–Cu bimetallic catalysts. We observed that changing the Cu content in the catalysts causes charge redistribution which results in a negative correlation with CO selectivity. Abstract : Highly selective CO2 electroreduction to CO (∼90% faradaic efficiency) was achieved on NiCu0.25 bimetallic nanoparticle catalysts. By combining Synchrotron based X-ray absorption and in situ Raman spectroscopy studies, we found that there is a negative correlation between the Cu content in NiCu x and CO selectivity due to redistribution of the 3d electrons.